Challenges and Opportunities In Teaching English In Online Learning: a Case Study at MTs NW Boro Tumbuh In Academic Year 2021/2022 - M Rian Afriandi; Kamaluddin Kamaluddin; Lalu Ali Wardana (Syntax Corporation, 2022)
Pandemics are the most extensively reported in 2020, with implications for a variety of industries. Due to the emergency situation produced by the pandemic, many countries have shuttered major sectors, including education. Since then, governments throughout the world have enacted lockdowns in various countries dependent on the severity of the epidemic to guarantee that its spread is limited and the curve flattens. The study aims to Analyze the challenges and opportunities in teaching English in online learning: a study case at MTS NW Boro Tumbuh in academic year 2021/2022. This type of research is descriptive qualitative research. The results of study show that the challenge of teaching English online has various challenges as like: the challenge is a little complicated when compared to the WA group, the complicated E-Learning is too much space compared to the WA group, the difficulty with internet interference From the application, Using the application is a bit difficult In terms of adapting to teaching that is different from conventional methods and when dealing with students, sometimes when learning English begins they are just absent and do not open the learning material and some are late in delivery and make for various reasons.